EXPERIMENTAL STUDY AND ANALYSIS OF POWER QUALITY MEASUREMENT OF PHOTOVOLTAIC CELLS WITH VARIOUS PARAMETERS - Dwivedi, Smriti; Bhatt, Sunil (International Journal of Engineering Technologies and Management Research, 2016)
The Solar panels are on a mount that follows the sun. These are optimizing output by following the sun across the sky for maximum sunlight. These typically give you about a 15% increase in winter and up to a 35% increase in summer. This is just the opposite of the seasonal variation for MPPT controllers. Since panel temperatures are much lower in winter, they put out more power. And winter is usually when you need the most power from your solar panels due to shorter days. Maximum Power Point Tracking is electronic tracking - usually digital. The charge controller looks at the output of the panels, and compares it to the battery voltage.